Izzivi managementa talentov (University of Maribor Press, 2025)
Talent Management Challenges. The scientific monograph Talent Management Challenges addresses key aspects of talent development and management in contemporary organizations. Across seven chapters, the authors explore the interconnection between effort, talent, personality traits, teamwork, aging employees, and the validation of HR tools. The publication integrates psychological, organizational, and leadership perspectives and demonstrates how organizations can create effective strategies for talent development and retention. The purpose of the monograph is to encourage reflection on the importance of human capital for long-term success, social responsibility, and innovation. The work, authored by sixteen contributors from diverse academic and research backgrounds, represents a significant contribution to the theoretical and practical understanding of talent management.